2015
DOI: 10.1007/s12185-015-1854-5
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation in non-Hodgkin lymphoma

Abstract: The present study analyzed the incidence and clinical features of disseminated intravascular coagulation (DIC) developed in association with non-Hodgkin lymphoma (NHL). Two hundred thirty-six patients with newly diagnosed NHL were admitted to our institute since Jul. 2008 to Dec. 2014. Coagulation markers were evaluated in 161 of 236 patients at the time of diagnosis. DIC was diagnosed in 18 patients (11.2 %) based on the criteria established by Ministry of Health, Labor, and Welfare of Japan. All of the 18 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As for the liver dysfunction in hematological disease with DIC, Chi S et al reported that Liver dysfunction in ML such as bilirubin, aminotransferases, serum choline esterase, and albumin levels, were worse in patients with DIC than those without DIC, indicating impaired production of coagulation factors [33]. Furthermore, DIC exerts significantly negative impact on prognosis of non-Hodgkin lymphoma [33]. Similarly, in our present study, the liver dysfunction had significant impact for the degree of accordance between DIC resolution and treatment outcome in ML.…”
Section: Importance Of Dic Resolution For Os Regardless Of Any Backgrmentioning
confidence: 99%
“…As for the liver dysfunction in hematological disease with DIC, Chi S et al reported that Liver dysfunction in ML such as bilirubin, aminotransferases, serum choline esterase, and albumin levels, were worse in patients with DIC than those without DIC, indicating impaired production of coagulation factors [33]. Furthermore, DIC exerts significantly negative impact on prognosis of non-Hodgkin lymphoma [33]. Similarly, in our present study, the liver dysfunction had significant impact for the degree of accordance between DIC resolution and treatment outcome in ML.…”
Section: Importance Of Dic Resolution For Os Regardless Of Any Backgrmentioning
confidence: 99%
“…DIC worsens the clinical outcome of lymphomas and is associated with an elevated, though not prohibitive, surgical risk [21] ; on the other hand, the cornerstone of cancer-associated DIC is the treatment of the underlying disorder. In the present case, the benefits of performing a splenectomy clearly outweighed the risks.…”
Section: Discussionmentioning
confidence: 99%
“…Heparinoids, including low-molecular-weight heparin (LMWH) and unfractionated heparin (UFH), synthetic serine protease inhibitors, antithrombin products, and recombinant human soluble thrombomodulin (rTM), are approved for the treatment of DIC in Japan. The levels of AT remain within the normal range in most cases of DIC caused by haematological malignancies except for malignant lymphoma (ML) [5,44]. In one study, all malignant lymphoma patients with DIC (n = 18) were at an advanced clinical stage with bone marrow involvement [5].…”
Section: Treatment Of Dic Caused By Haematological Malignancymentioning
confidence: 99%
“…(1) Procoagulant activity Hypercoagulability is present in patients with haematological malignancy-associated DIC, as an increase in plasma levels of coagulation markers such as the thrombin-antithrombin complex (TAT) and soluble fibrin monomer (SF) are noted in these patients [5,[8][9][10][11]. Leukaemia cells aberrantly express tissue factor (TF), which interacts with factor VII and orchestrates the extrinsic coagulation cascade, leading to the production of thrombin, which converts fibrinogen to fibrin, causing fibrin deposition [3].…”
Section: The Pathogenesis Of Dic Caused By Haematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation